Effect of the Happy Mom Application on Pregnant Women’s Knowledge of Fetal Development - Nurul Komariah; Sari Wahyuni (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Stimulation is crucial for development during the first 1,000 days; a lack of stimulation can lead to developmental delays. Parents’ knowledge influences the stimulation they provide. One way to improve mothers’ knowledge of fetal development is to provide education to pregnant women. With advances in technology, mobile apps have emerged as innovative solutions for prenatal education. Based on a survey of pregnancy apps around 2020, most of them were iOS-based. Meanwhile, the majority of users in Indonesia are Android users. Happy Mom is an Android app. The aim is to assess the impact of the education provided through Happy Mom on mothers’ knowledge. Methods: The design was a quasi -experimental, one-group pre-post test design. The sample consisted of all pregnant women who checked in at PMB Teti Herawati in 2021, were present at the time of the study, and met the inclusion and exclusion criteria. The sampling technique was non-probability sampling. Purposive sampling. The sample is 34 respondents. Results: Of the 34 respondents (100%), there is a difference of 3 points in the median score between pre- and post-test knowledge. The maximum score increased by 1 point. The results of the statistical test show a p-value of 0.001. Education via the Happy Mom app has an effect on the knowledge of pregnant women. Conclusion: The Happy Mom app has the potential to improve knowledge of expectant mothers. It is recommended that further studies with a more robust design be conducted.